2019
DOI: 10.1016/j.cmi.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Developing the concept of beneficial non-specific effect of live vaccines with epidemiological studies

Abstract: Background and objectives Epidemiological and immunological studies are increasingly reporting non-specific effects (NSEs) of vaccines; i.e. vaccines may affect the risk and severity of non-targeted infections. We reviewed how epidemiological studies developed the concept of beneficial NSEs of live vaccines. Sources This is a personal narrative of how we came to pursue the concept of NSEs in studies of measles vaccine (MV) from the late 1970s. We also searched Pubmed for epidemiological studies of non-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 77 publications
1
57
0
4
Order By: Relevance
“…However, numerous immunological studies have concluded that a vaccine can have a non specific protective effect. 1 At the beginning of the 20 th century, Calmette already noted that children vaccinated with BCG had a lower mortality rate 1 . Since then may have been born the principle of non specific effects of BCG vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous immunological studies have concluded that a vaccine can have a non specific protective effect. 1 At the beginning of the 20 th century, Calmette already noted that children vaccinated with BCG had a lower mortality rate 1 . Since then may have been born the principle of non specific effects of BCG vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This means that it may have effects on infections not targeted by the vaccine. 1 Observationl studies found that Bacillus Calmette Guerin (BCG) vaccination is associated with reduced non specific mortality and better survival 1 . Other immunological studies demonstrated that BCG can induce trained innate immuniy.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of CMI, five narrative reviews offer recent insights on innate and adaptive immune memory, shedding light on specific and nonspecific effects of vaccines against a variety of pathogens. Benn and Aaby [9] describe in an historical review how epidemiologic studies in many industrialized and low-income countries led to the concept of beneficial nonspecific effects of BCG and other live human vaccines. Koeken et al [10] discuss the epidemiologic evidence and biologic concepts of early clearance of M. tuberculosis by BCG vaccination.…”
mentioning
confidence: 99%
“…This feature in the SARS-CoV-2 protein sequence may be a pointer to support the idea of using the MMR vaccine in COVID-19 as floated by Fidel and Noverr [15] and the use of recombinant ACE2 by Kruse [16] as a preventive measure to reduce the inflammation in COVID-19 patients. The use of drugs/vaccines for existing viruses in managing untreatable viral diseases has been suggested by others also [17,18] including for COVID-19 [19].…”
Section: Resultsmentioning
confidence: 99%